Factors Influencing Financial Management Behavior among Small and Medium Enterprise Operators in the Jaffna District, Sri Lanka - Mithila, G.; Kengatharan, L.; Yathurshan, N. (Sri Lanka Finance Association, 2025)
Effective financial management is important for the sustainability of small and medium sized enterprises (SMEs). This study examines whether financial knowledge, financial attitudes and locus of control influence the financial management behaviour of SMEs business operators in Jaffna, Sri Lanka. A stratified random sample of 150 registered SME owners and managers was surveyed using a structured questionnaire. Descriptive statistics, correlation analysis and multiple regression were employed to analyse relationships between variables. The results show that financial knowledge and financial attitudes both have positive and statistically significant effects on SMEs’ financial management behaviour. Operators with greater financial literacy and more favorable financial attitudes tend to engage in more prudent financial practices. In contrast, locus of control, the degree to which individuals feel in control of financial outcomes, was not a significant factor of financial behaviour in this context. These findings highlight the importance of enhancing financial literacy and improving positive financial attitudes among SME operators, while also suggesting that broader external factors may moderate the role of personal control. The study integrates these results with contemporary financial behaviour theory and evidence, discusses practical interventions such as targeted financial education and attitude oriented programs and outlines implications for policy makers and future research. The insights contribute to the literature on SME financial management in emerging economies and provide guidance for improving financial practices to support the growth and sustainability of SMEs in regions like Jaffna.
Keywords: Financial attitude; Financial knowledge; Financial management behaviour; Locus of control; SMEs; Jaffna